TWO NEW SPECIES OF AMOMUM (ZINGIBERACEAE) FROM WESTERN GHATS, INDIA - Thomas, V. P.; Sabu, M. (Edinburgh Journal of Botany, 2012)
Two new species of Amomum, A. agastyamalayanum V.P.Thomas & M.Sabu and A. newmanii M.Sabu & V.P.Thomas (Zingiberaceae), from the Western Ghats of Kerala are described and illustrated. Their distribution, ecology, IUCN status, etymology and similarities to related taxa are also discussed.
Keywords: Amomum; India; Kerala; new species; Western Ghats; Zingiberaceae